THE INFLUENCE OF PERSONAL SELLING, ONLINE CUSTOMER REVIEWS, AND RELIGIOSITY ON PURCHASE DECISIONS DURING IN THE COVID-19 PANDEMIC THROUGH ATTITUDE - Sari, Danang Ario; Utomo, Budi (UIN Salatiga, 2021)
This study aims to determine the effect of personal selling, online customer reviews, and religiosity on purchasing decisions during the Covid-19 pandemic by affirming attitudes as intervening variables. Case study of Consumers at the Central Handicraft Industry of Wood, Horn and Bone in Magelang. The data collection method in this study was carried out through a questionnaire distributed to buyers and users of handicrafts. The sample taken was 100 respondents, the analytical tool used is multiple linear regression analysis with the SPSS 16.0 application. The method of analysis in this study uses path analysis to determine the effect after being mediated by the attitude variable. The results of regression analysis in this study indicate that personal selling and online customer reviews have a positive and insignificant effect on purchasing decisions but religiosity has a significant positive effect on purchasing decisions. Then personal selling and online customer reviews have a positive and insignificant effect on attitudes but religiosity has a significant positive effect on attitudes. In the path analysis test, the attitude variable is able to mediate the effect of online customer reviews and religiosity on purchasing decisions, while the inability to mediate the effect of personal selling on purchasing decisions.